Molecular Diagnosis of Pseudomonas Aeruginosa Isolated from Urinary Tract Infections and Evaluation of the Effect of Solanum Nigrum Extract on its Growth - Inas Ahmed Zaynal; Randa Salim Bayat; Shanay A. Mohammed (American Journal of Biomedicine and Pharmacy, 2025)
Background & aim: Antimicrobial resistance, biofilm formation, and a number of other virulence features make Pseudomonas aeruginosa a well-known gram-negative pathogenic bacterium. So, this study was aimed to molecular diagnosis of P. aeruginosa isolated from urinary tract infections and evaluation of the effect of Solanum nigrum extract on its growth. Materials & Methods: During November 2024 to February 2025, 140 clinical samples of who had been admitted to Kirkuk Hospital in Kirkuk City after consulting with a specialist physician and being sent to the laboratory were gathered. The samples were then brought directly to the laboratory for culture on culture media. Results: The findings demonstrated that, when grown in the optimal culture medium, 34 (24.3%) of the total samples had favorable results for bacterial growth. Out of all the samples, 106 (75.7%) had negative bacterial growth results. P. aeruginosa was highly responsive to gentamicin (82.3%), imipenem (91.2%), amikacin (97.1%), and ampicillin (88.3%). However, P. aeruginosa was 100% responsive to tobromycin. The findings showed that the ability of S. nigrum for bacteria inhibition, where the 50ul concentration showed the least efficiency against P. aeruginosa, as the diameter of the inhibition zone reached 6.13±1.07mm, while the 75ul concentration showed the highest inhibition, reaching 16.1±1.8mm, and the highest inhibition zone was recorded at the 100ul concentration, reaching 29.12±3.7mm. In the current study from 34 isolate, 34(100.0%) Pseudomonas aeruginosa isolates possessed 16S RNA gene. Conclusion: P. aeruginosa isolates are resistant to most antibiotics, with amikacin and topromycin being the most effective. S. nigrum extract exhibits antibacterial activity, and the 16S rRNA gene is a reliable marker for isolate identification.